Functionalization of chemically derived graphene for improving its electrocapacitive energy storage properties - Lei, Zhibin; Zhang, Jintao; Zhang, Li Li; Kumar, Nanjundan Ashok; Zhao, X. S (Energy & environmental science, 2016)
Chemically derived graphene holds great promise as an electrode material for electrochemical energy storage owing to its unique physical and chemical properties. Recent years have witnessed tremendous research breakthroughs in the field of graphene-based materials for electrochemical capacitors. This article presents a review of the latest developments in the functionalization of chemically derived graphene for improving its electrocapacitive properties. Beginning with a brief description of supercapacitors, graphene, and chemically derived graphene, we discuss the preparation, electrocapacitive properties, and drawbacks of chemically derived graphene and its derivatives, followed by a discussion on how to functionalize chemically derived graphene for improving its double-layer capacitance and pseudocapacitance. Emphasis is made on comparing and highlighting demonstrated approaches to functionalizing chemically derived graphene. Future research towards developing advanced electrochemical capacitors, perspectives and challenges are outlined. This review summarizes the latest developments in the functionalization of chemically derived graphene for improving its electrocapacitive performance.